(3GdbGfhf GdEOGQj h MeGjI GdUMI GdYGeI (B:s (3OQGSI ebGQfI (B/s - (3GeGe, eMeO eMeO YHOgs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2007)
(3GdHGH GdGhd (B: (3GdMeGjI GdbGfhfjI ddMb aj SdGeI GdZPGA GdMeGjI GdbGfhfjI ddZPGA ef GdJdhK ZjQ GdYeOj , GdMeGjI GdbGfhfjI ef GdJdhK GdYeOj , GdGKGQ GdfGTFI Yf GdJdhK GdZPGFj GdHGH GdKGfj GdVeGfGJ GdJTQjYjI hGdYedjI dSdGeI GdZPGA eaghe GdVHW hCfhGYg hgjFGJg , hSGFd GdVHW GdGOGQj hCSGdjHg `C ZQGV GdVHW GdGOGQj aj eLGd MeGjI GdZPGA , hMOI GdbGfhf CKQgG aj aGYdjI GdVHW GdGOGQj , GdMSHI GdGSdGejI hMeGjI GdZPGA , GdfXe GdeTGQcI aj MeGjI GdZPGA s
Keywords: (3GdUMI GdYGeIs; (3GdUMI GdYGeI(B- (3bhGfjf hJTQjYGJ s; (3GdbGfhf GdGOGQjs